HUBUNGAN POWER OTOT LENGAN DAN KEKUATAN PERGELANGAN TANGAN TERHADAP HASIL TEMBAKAN DARI SAMPING BADAN (SIDE SHOOT) - Yamani, Ahmad Ilham (STKIP Pasundan, 2017)
This research was conducted with the aim to study the relationship of arm strength and fighting strength to the side shot results. This study discusses the presence or absence of a relationship. The method used in this research is descriptive research method with quantitative research. In this study data collection techniques using the test, for arm strength using the ball medicine test, for the strength of the battle using the hand grip test. The population used in this study were 12 members of the STKIP Pasundan Cimahi Student Activity Unit (UKM). Based on the research data, the results of the experimental arm strength and side shoot results are as broad as 0.1643, then the arm muscle strength has a positive relationship to the side shoot results. To challenge the existing power and the side shot result of 0.5534, the strength of hand combat has a positive relationship with the side shot result. And to fight the strength of the arm muscles and the strength of the side shot results as broad as 0.7439, the strength of the muscles together with the strength of the hand gives a positive influence on the results of the side shot. It can be interpreted that good arm muscle strength and hand strength will be presented with good side firing results too.